# lim sup a simple inequality

I´m not sure how to start with this proof, how can I do it? $$\limsup ( a_n b_n ) \leqslant \limsup a_n \limsup b_n$$ I also have to prove, if $\lim a_n$ exists then: $$\limsup ( a_n b_n ) = \limsup a_n \limsup b_n$$ Help please, it´s not a homework I want to learn.

-
In both cases you need the assumption $a_n\geq0$ and $b_n\geq0$ (for $n$ large enough). (Can you see some counterexamples?) – AD. Feb 25 '12 at 6:48

## 3 Answers

• The inequality is a part of Problem 2.4.17 in the book Wieslawa J. Kaczor, Maria T. Nowak: Problems in mathematical analysis: Volume 1; Real Numbers, Sequences and Series, Problem 2.4.15. The problem is given on p.44 and solved on p.200-201. (AFAIK this book is also available in French and Polish.) See also this answer.

I am making this CW, feel free to add other references.

-

The basic idea is what could be called the monotonicity of $\sup$: the supremum over a set is at least as large as the supremum over a subset.

Recall the definition of $\limsup$: $$\limsup_{n\to\infty}a_n=\lim_{k\to\infty\vphantom{d^{d^a}}}\sup_{n>k}a_n\tag{1}$$ The limit in $(1)$ exists since, by the monotonicity of $\sup$, $\sup\limits_{n>k}a_n$ is a decreasing sequence.

Furthermore, also by the monotonicity of $\sup$, $$\sup_{n>k}a_n \sup_{n>k}b_n=\sup_{m,n>k}a_nb_m\ge\sup_{n>k}a_nb_n\tag{2}$$ Taking the limit of $(2)$ as $k\to\infty$ yields $$\limsup_{n\to\infty}a_n\limsup_{n\to\infty}b_n\ge\limsup_{n\to\infty}a_nb_n\tag{3}$$ since the limit of a product is the product of the limits.

If the limit of $a_n$ exists, we have that for any $\epsilon>0$, there is an $N$, so that $n>N$ implies $$a_n\ge\lim_{n\to\infty}a_n-\epsilon\tag{4}$$ Thus, for $k>N$, $$\sup_{n>k}a_nb_n\ge\left(\lim_{n\to\infty}a_n-\epsilon\right)\sup_{n>k}b_n\tag{5}$$ taking the limit of $(5)$ as $k\to\infty$ yields $$\limsup_{n\to\infty}a_nb_n\ge\left(\lim_{n\to\infty}a_n-\epsilon\right)\limsup_{n\to\infty}b_n\tag{6}$$ Since $\epsilon$ is arbitrary, $(6)$ becomes $$\limsup_{n\to\infty}a_nb_n\ge\lim_{n\to\infty}a_n\limsup_{n\to\infty}b_n\tag{7}$$ Combining $(3)$ and $(7)$ yields $$\limsup_{n\to\infty}a_nb_n=\lim_{n\to\infty}a_n\limsup_{n\to\infty}b_n\tag{8}$$ since $\displaystyle\limsup_{n\to\infty}a_n=\lim_{n\to\infty}a_n$.

-

I assume all relevant values are positive as otherwise this is false. Note that whenever $\limsup(a_nb_n)$ exists, we have some subsequence $(a_n'b_n')$ of $(a_nb_n)$ which converges to $\limsup(a_nb_n)$. For any $\epsilon>0$, we have some $N$ such that $$k\geq N\implies a_k'b_k'>\limsup(a_nb_n)-\epsilon\text{ and } b_k'<\limsup(b_n)+\epsilon$$ and so we have $$k\geq N\implies a_k'>\frac{\limsup(a_nb_n)-\epsilon}{b_k'}>\frac{\limsup(a_nb_n)-\epsilon}{\limsup(b_n)+\epsilon}$$ and this goes to $\frac{\limsup(a_nb_n)}{\limsup(b_n)}$ as $\epsilon\to 0,k\to\infty$ giving us $\limsup(a_n)\geq \frac{\limsup(a_nb_n)}{\limsup(b_n)}$ so $$\limsup(a_n)\limsup(b_n)\geq \limsup(a_nb_n).$$ I will leave the case where $\lim\limits_{n\to\infty}(a_n)$ exists to you, as it is similar.

-
 @AD. Yes, you're quite right. Fixed. – Alex Becker Feb 25 '12 at 6:58